CELL PHONES KEEP YOU IN CELL - Losini, A Muthu Meena (PEOPLE: International Journal of Social Sciences, 2019)
The objective of the paper is to expose the effect of the overuse of mobile phones in the family and it also reveals how it affects the relationship among the family members. As the writer of this paper is from a typical Tamil culture in India where relationships are valued, this issue has been taken. At present, the overuse of mobile phones strangles the relationship within the family in our community and which reflects the degradation in the family and the society. It has been explained how the extended family is shattered and how it terrifically affects the young generation. The paper also explores how the family and the society are spoiled. It tends to create awareness in the young minds towards the proper use of mobile phones and to safeguard the values and virtues of our community in the family, a minor unit of society.